A review on the stability and surface modification of layered transition-metal oxide cathodes. (June 2021) - Kim, Ju-Myung; Zhang, Xianhui; Zhang, Ji-Guang; Manthiram, Arumugam; Meng, Ying Shirley; Xu, Wu
Graphical abstract: Abstract: An ever-increasing market for electric vehicles (EVs), electronic devices and others has brought tremendous attention on the need for high energy density batteries with reliable electrochemical performances. However, even the successfully commercialized lithium (Li)-ion batteries still face significant challenges with respect to cost and safety issues when they are used in EVs. From a cathode material point of view, layered transition-metal (TM) oxides, represented by LiMO2 (M = Ni, Mn, Co, Al, etc .) and Li-/Mn-rich x Li2 MnO3 ·(1– x )LiMO2, have been considered as promising candidates because of their high theoretical capacity, high operating voltage, and low manufacturing cost. However, layered TM oxides still have not reached their full potential for EV applications due to their intrinsic stability issues during electrochemical processes. To address these problems, a variety of surface modification strategies have been pursued in the literature. Herein, we summarize the recent progresses on the enhanced stability of layered TM oxides cathode materials by different surface modification techniques, analyze the manufacturing process and cost of the surface modification methods, and finally propose future research directions in this area.